Unusual and severe peripartum cardiomyopathy: A case report - B, Lamanna; M, Vinciguerra; FM, Crupano; R, Cicinelli; E, Cicinelli; A, Vimercati (Journal of Cardiology and Cardiovascular Medicine, 2021)
Peripartum cardiomyopathy (PPCM) is a relatively rare cardiac disease that manifests in the final stage of pregnancy and in the first months after delivery in women with no preexisting heart disease. Many etiological processes have been suggested: viral myocarditis, abnormal immune response to pregnancy, excessive prolactin excretion, prolonged tocolysis and a familiar predisposition to PPCM. Its diagnosis is often delayed because its symptoms, which include fatigue, dyspnea and palpitations are nonspecific. For this reason the diagnosis of PPCM is still made by exclusion of other etiologies. The long-term prognosis, once the acute phase is over, is a function of myocardial damage, this varies from complete functional recovery to chronic HF. The outcome of PPCM is highly variable with an alevated risk of fetomaternal morbidity and mortality. We report a serious case of a 40 years old female with biamniotic bicorionic twin pregnancy (PMA) who delivered by caesarean section and developed acute PPCM on post-operative. Symptoms occurred two hours after an intramuscular injection of two vials of methylergonovine the same day of cesarean delivery. These manifested in sudden tachypnoe, tachycardia and the appearance itchy maculopapular rash on her chest. On further evaluation, ECHO revealed cardiomegaly with reduced ejection fraction (< 15%). The case was successfully managed by a multidisciplinary team, using drugs like levosimendan and cabergoline, which rapresent emerging strategy in this clinical context.